A battery terminal performance simulation test structure and method

Through the design of the integrated cast molded terminals and glue layer of copper core and lead-based, combined with the fixing of V-shaped clamps, the problem that the copper core and lead-based cannot move relative to each other in the existing technology is solved, and more accurate torque testing is achieved, improving the Test accuracy and product quality.

CN111579480BActive Publication Date: 2024-12-31ZHEJIANG TIANNENG BATTERY (JIANGSU) CO LTD +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202010529881.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-06-11
Publication Date
2024-12-31
Estimated Expiration
2040-06-11

AI Technical Summary

Technical Problem

In the prior art, the copper core is embedded in the lead base body, and the vice clamps the copper core when clamps the lead base, resulting in the copper core being unable to produce relative motion with the lead base body. The torque tested cannot accurately reflect the torque of the terminal, causing errors. Verdict.

Method used

The columnar terminals are cast in one-piece cast with copper core and lead-based components. The copper core and lead-based components are separated by rubber mold and glue layer. The V-shaped clamp is used to ensure that the vise only clamps the copper cap but not clamps during testing. Copper core, combined with high temperature curing glue layer to improve the accuracy of the test.

Benefits of technology

The accuracy of the copper core torque test is improved, and the problem of the vice clamping the lead base at the same time is avoided, which enhances the accuracy of the experimental data and the product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111579480B_ABST
    Figure CN111579480B_ABST
Patent Text Reader

Abstract

The present invention discloses a battery terminal performance simulation test structure and method, including a columnar terminal integrally cast by copper core and lead base, wherein the copper core is embedded in the lead base, and the bottom of the terminal is integrally connected with a connecting block, and also includes a rubber mold, a glue layer, and a vise. The rubber mold is open at the top, cylindrical, and has a through hole at the bottom. The terminal passes through the through hole from bottom to top, and a glue layer is provided between the inner wall of the rubber mold and the outer wall of the terminal; the glue layer is solidified and attached to the outer wall of the terminal, and the rubber mold is opened, and the terminal attached with the glue layer is placed in the left and right clamps of the vise. It can be seen from the structure of the present invention that by injecting glue into the gap between the rubber mold and the outer side of the terminal, a glue layer attached to the outer side of the lead base is formed, so that during the torque test, the vise will not clamp the copper core and the lead base at the same time, and the operation is simple and fast, which greatly improves the accuracy of the experimental data and the quality rate of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of battery terminal testing, and in particular to a battery terminal performance simulation testing structure and method. Background Art

[0002] Terminals are important parts of batteries, which are used to connect external devices and conduct current. For the sake of aesthetics and connection reliability, the terminals of existing batteries are composed of copper core and lead base. If the copper core and lead base are not firmly combined, the copper core will loosen, bringing quality risks, so the inspection of terminals is particularly important.

[0003] At present, a vise is used to clamp the lead-based body, and then the copper core is tested for torque. Because the copper core is embedded in the lead-based body, the vise clamps the copper core while clamping the lead base, so that the copper core cannot move relative to the lead-based body. Therefore, the tested torque cannot accurately reflect the torque of the terminal, which leads to misjudgment. Summary of the invention

[0004] The purpose of the present invention is to provide a battery terminal performance simulation test structure and method thereof, so as to overcome the defects of the prior art and solve the problem that the copper core is embedded in the lead-based body, and the vise clamps the lead base and the copper core at the same time, so that the copper core cannot produce relative movement with the lead-based body, so the tested torque cannot accurately reflect the torque of the terminal, thereby causing misjudgment.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A battery terminal performance simulation test structure and method, comprising a columnar terminal integrally cast by a copper core and a lead base, wherein the copper core is embedded in the lead base, and a connecting block is integrally connected to the bottom of the terminal, and further comprising a rubber mold, a glue layer, and a vise, wherein the rubber mold is cylindrical with an upper opening and a through hole passing through the bottom, and the terminal passes through the through hole from bottom to top, and a glue layer is provided between the inner side wall of the rubber mold and the outer side wall of the terminal;

[0007] The glue layer is solidified and attached to the outer side wall of the terminal, the rubber mold is opened, and the terminal attached with the glue layer is placed in the left and right clamping plates of the vise.

[0008] Furthermore, a skirt is vertically extended downward along the inner periphery of the through hole.

[0009] Furthermore, the through hole and the skirt are interference fit with the outer wall of the lead base.

[0010] Furthermore, the skirt is just stuck on the top surface of the connecting block.

[0011] Furthermore, the longitudinal section of the copper core is T-shaped, and is divided into a copper cap and a copper rod. A cylindrical hole is provided in the center of the lead base, the copper rod is embedded in the cylindrical hole, and the copper cap is placed on the top surface of the lead base.

[0012] Furthermore, the outer diameter of the copper cap is equal to the outer diameter of the lead base.

[0013] Furthermore, the height of the top surface of the glue layer is lower than the height of the connection between the copper cap and the top surface of the lead base.

[0014] Furthermore, the glue layer is made of epoxy resin.

[0015] Furthermore, V-shaped clamping blocks are fixed on the inner side surfaces of the left and right clamping plates of the vise through embedded bolts, and the openings of the V-shaped clamping blocks are arranged opposite to each other.

[0016] A test method for a battery terminal performance simulation test structure, comprising:

[0017] S1: Pass the terminal 1 through the through hole 21 of the rubber mold 2 and place it on the workbench surface (the workbench surface is horizontal);

[0018] S2: Inject glue into the gap between the inner wall of the rubber mold 2 and the outer wall of the terminal 1, and the glue liquid level is 2mm to 4mm lower than the height of the bonding line between the copper cap 14 and the top surface of the lead base 12;

[0019] S3: Put the rubber mold 2 injected with glue, together with the copper core 11 and the lead base 12, into a high temperature box at 60°C to 80°C, cure for 70 min to 120 min, take out and cool to room temperature;

[0020] S4: peeling off the rubber mold 2 (demolding) to expose the terminal 1 with the glue layer 3 attached thereto, wherein the rubber mold 2 can be reused;

[0021] S5: The V-shaped clamping block 6 is fixed to the inner side surfaces of the left and right clamping plates of the vise 4 by means of the embedded bolts 5, and the openings of the V-shaped clamping block 6 are arranged opposite to each other;

[0022] S6: Put the demoulded terminal 1 into the left and right clamps of the vise 4, and make the glue layer 3 just clamped between the V-shaped clamping blocks 6, so as to lock the lead base 12;

[0023] S7: Draw a vertical marking line 7 at the junction line between the copper cap 14 and the top surface of the lead base 12, that is, half of the marking line 7 is located on the outer surface of the copper cap 14, and the other half is located on the outer surface of the lead base 12;

[0024] S8: Use the "torque handle" to perform a torque test on the copper core, that is, the "torque handle" clamps the copper cap 14 and rotates it horizontally. If the torque of the copper core 11 meets the standard, the marking line 7 will not be relatively misaligned, otherwise, misalignment will occur.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The present invention provides a battery terminal performance simulation test structure and method thereof. A glue layer is provided between the inner wall of the rubber mold and the outer wall of the terminal, and the glue layer is solidified and attached to the outer wall of the terminal. The rubber mold is opened, and the terminal with the glue layer attached is placed in the left and right clamping plates of the vise. This can avoid the problem of the vise clamping the copper core while clamping the lead base, thereby improving the accuracy of the copper core torque test.

[0027] 2. The present invention provides a battery terminal performance simulation test structure and method, wherein a skirt is vertically extended downward along the inner peripheral edge of the through hole, so as to extend the contact surface between the inner wall of the through hole and the outer wall of the terminal, thereby preventing liquid glue from seeping out of the through hole.

[0028] 3. The present invention provides a battery terminal performance simulation test structure and method, in which the through hole and the skirt are interference fit with the outer wall of the lead base, which further improves the air tightness between the inner wall of the through hole, the inner wall of the skirt and the outer wall of the terminal, making it more difficult for glue to seep out from the bottom of the skirt.

[0029] 4. The present invention provides a battery terminal performance simulation test structure and method, wherein a connecting block is integrally connected to the bottom of the terminal, and the skirt is just stuck on the top surface of the connecting block, so as to facilitate the control of the distance that the rubber mold passes through the through hole.

[0030] 5. The present invention provides a battery terminal performance simulation test structure and method thereof, wherein the height of the top surface of the glue layer is lower than the height of the connection between the copper cap and the top surface of the lead base. In this way, when the vise clamps the glue layer (i.e., clamps the lead base), the copper core will not be clamped at the same time, thereby avoiding the problem of the vise clamping the copper core while clamping the lead base, thereby improving the accuracy of the copper core torque test.

[0031] 6. The present invention provides a battery terminal performance simulation test structure and method thereof, wherein V-shaped clamping blocks are fixed on the inner sides of the left and right clamping plates of the vise by embedded bolts, and the openings of the V-shaped clamping blocks are arranged opposite to each other, and the demoulded terminal is placed between the V-shaped clamping blocks and clamped firmly and securely. When testing the torque of the copper core, the relative position between the V-shaped clamping opening and the outer side of the glue layer is not easily rotated.

[0032] 7. The present invention provides a battery terminal performance simulation test structure and method thereof, which injects glue into the gap between the rubber mold and the outer side of the terminal to form a glue layer attached to the outer side of the lead base, so that during the torque test, the vise will not clamp the copper core and the lead base at the same time. The operation is simple and quick, which greatly improves the accuracy of the experimental data and the quality rate of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a schematic front cross-sectional view of the present invention when injecting glue.

[0034] Figure 2 It is a schematic front cross-sectional view after demoulding of the present invention.

[0035] Figure 3 This is a top view schematic diagram of the terminal test clamping of the present invention.

[0036] In the figure, 1 is a terminal, 11 is a copper core, 12 is a lead base, 13 is a connecting block, 14 is a copper cap, 15 is a copper rod, 16 is a cylindrical hole, 2 is a rubber mold, 21 is a through hole, 22 is a skirt, 3 is a glue layer, 4 is a vise, 5 is an embedded bolt, 6 is a V-shaped clamp, and 7 is a marking line. DETAILED DESCRIPTION

[0037] The present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the invention by those skilled in the art all fall within the scope defined by the claims attached to this application.

[0038] Example 1: Figures 1 to 3 The battery terminal performance simulation test structure and method shown in the figure include a columnar terminal 1 integrally cast by a copper core 11 and a lead base 12, wherein the copper core 11 is embedded in the lead base 12, and a connecting block 13 is integrally connected to the bottom of the terminal 1, and further include a rubber mold 2, a glue layer 3, and a vise 4. The rubber mold 2 is cylindrical with an upper opening and a through hole 21 passing through the bottom, and the terminal 1 passes through the through hole 21 from bottom to top, and a glue layer 3 is provided between the inner wall of the rubber mold 2 and the outer wall of the terminal 1; the glue layer 3 is cured and attached to the outer wall of the terminal 1, and the rubber mold 2 is opened, and the terminal 1 attached with the glue layer 3 is placed in the left and right clamps of the vise 4; a skirt 22 is vertically extended downward along the inner peripheral edge of the through hole 21; the skirt 22 is interference fit with the outer wall of the lead base 12; and the skirt 22 is just stuck on the top surface of the connecting block 13.

[0039] The copper core 11 has a T-shaped longitudinal section, which is divided into a copper cap 14 and a copper rod 15. A cylindrical hole 16 is provided in the center of the lead base 12, and the copper rod 15 is embedded in the cylindrical hole 16. The copper cap 14 is placed on the top surface of the lead base 12. The outer diameter of the copper cap 14 is equal to the outer diameter of the lead base 12. The height of the top surface of the glue layer 3 is lower than the height of the connection between the copper cap 14 and the top surface of the lead base 12. The glue layer 3 adopts an "epoxy resin" cured glue layer. V-shaped clamping blocks 6 are fixed on the inner sides of the left and right clamping plates of the vise 4 through embedded bolts 5, and the openings of the V-shaped clamping blocks 6 are arranged opposite to each other.

[0040] The vise 4 involved in the present invention adopts a precision angle-fixed vise of model SAV-6 provided by Omate Electromechanical Equipment Co., Ltd.

[0041] The testing method of the present invention is as follows:

[0042] S1: Pass the terminal 1 through the through hole 21 of the rubber mold 2 and place it on the workbench surface (the workbench surface is horizontal);

[0043] S2: Inject glue into the gap between the inner wall of the rubber mold 2 and the outer wall of the terminal 1, and the glue liquid level is 2mm to 4mm lower than the height of the bonding line between the copper cap 14 and the top surface of the lead base 12;

[0044] S3: Put the rubber mold 2 injected with glue, together with the copper core 11 and the lead base 12, into a high temperature box at 60°C to 80°C, cure for 70 min to 120 min, take out and cool to room temperature;

[0045] S4: peeling off the rubber mold 2 (demolding) to expose the terminal 1 with the glue layer 3 attached thereto, wherein the rubber mold 2 can be reused;

[0046] S5: The V-shaped clamping block 6 is fixed to the inner side surfaces of the left and right clamping plates of the vise 4 by means of the embedded bolts 5, and the openings of the V-shaped clamping block 6 are arranged opposite to each other;

[0047] S6: Put the demoulded terminal 1 into the left and right clamps of the vise 4, and make the glue layer 3 just clamped between the V-shaped clamping blocks 6, so as to lock the lead base 12;

[0048] S7: Draw a vertical marking line 7 at the junction line between the copper cap 14 and the top surface of the lead base 12, that is, half of the marking line 7 is located on the outer surface of the copper cap 14, and the other half is located on the outer surface of the lead base 12;

[0049] S8: Use the "torque handle" to perform a torque test on the copper core, that is, the "torque handle" clamps the copper cap 14 and rotates it horizontally. If the torque of the copper core 11 meets the standard, the marking line 7 will not be relatively misaligned, otherwise, misalignment will occur.

Claims

1. A battery terminal performance simulation test structure, comprising a columnar terminal (1) integrally cast by a copper core (11) and a lead base (12), wherein the copper core (11) is embedded in the lead base (12), and a connecting block (13) is integrally connected to the bottom of the terminal (1), characterized in that: The device also comprises a rubber mold (2), a glue layer (3), and a vise (4); the rubber mold (2) is cylindrical and has an opening at the top and a through hole (21) passing through the bottom; the terminal (1) passes through the through hole (21) from bottom to top; a glue layer (3) is provided between the inner wall of the rubber mold (2) and the outer wall of the terminal (1); the glue layer (3) is solidified and attached to the outer wall of the terminal (1); the rubber mold (2) is opened, and the terminal (1) attached with the glue layer (3) is placed in the left and right clamps of the vise (4); a skirt (22) extends vertically downward along the inner peripheral edge of the through hole (21); the through hole (21) and the skirt (22) are both interference fit with the outer wall of the lead base (12). The skirt (22) is just stuck on the top surface of the connecting block (13), the longitudinal section of the copper core (11) is T-shaped, and is divided into a copper cap (14) and a copper rod (15), the center of the lead base (12) is provided with a cylindrical hole (16), the copper rod (15) is embedded in the cylindrical hole (16), the copper cap (14) is placed on the top surface of the lead base (12), the top surface height of the glue layer (3) is lower than the height of the connection between the copper cap (14) and the top surface of the lead base (12), the glue layer (3) adopts "epoxy resin" curing glue layer, and V-shaped clamping blocks (6) are fixed on the inner side surfaces of the left and right clamping plates of the vise (4) through embedded bolts (5), and the openings of the V-shaped clamping blocks (6) are arranged opposite to each other.

2. A battery terminal performance simulation test structure according to claim 1, characterized in that: The outer diameter of the copper cap (14) is equal to the outer diameter of the lead base (12).

3. A test method for a battery terminal performance simulation test structure according to any one of claims 1 to 2, characterized in that: The method comprises: S1: passing the terminal (1) through the through hole (21) of the rubber mold (2) and placing the terminal (1) on a workbench surface, wherein the workbench surface is horizontal; S2: Inject glue into the gap between the inner wall of the rubber mold (2) and the outer wall of the terminal (1), with the glue liquid level being 2 mm to 4 mm lower than the height of the bonding line between the copper cap (14) and the top surface of the lead base (12); S3: Place the rubber mold (2) injected with glue, together with the copper core (11) and the lead base (12) in a high temperature box at 60°C to 80°C, cure for 70 min to 120 min, take out and cool to room temperature; S4: peeling off the rubber mold (2) and removing the mold to expose the terminal (1) attached with the glue layer (3), wherein the rubber mold (2) can be reused; S5: The V-shaped clamping block (6) is fixed to the inner side surfaces of the left and right clamping plates of the vise (4) by means of embedded bolts (5), and the openings of the V-shaped clamping block (6) are arranged opposite to each other; S6: Place the demoulded terminal (1) into the left and right clamps of the vise (4), and make the glue layer (3) just clamped between the V-shaped clamps (6), thereby locking the lead base (12); S7: Draw a vertical marking line (7) at the junction line between the copper cap (14) and the top surface of the lead base (12), that is, half of the marking line (7) is located on the outer surface of the copper cap (14), and the other half is located on the outer surface of the lead base (12); S8: Use a "torque handle" to perform a torque test on the copper core, that is, the "torque handle" clamps the copper cap (14) and rotates it horizontally. If the torque of the copper core (11) meets the standard, the marking line (7) will not be relatively misaligned, otherwise, misalignment will occur.